Konsentrasi pasar dan pertumbuhan aset terhadap Kinerja keuangan perbankan syariah - Herlina Dwi Rahmawati (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2018)
The research is conducted to examine the effect of market concentration and asset growth on thefinancial performance of Islamic banking in Indonesia. Data used in this study is obtained from thefinancial statement of Bank Indonesia publications and report of islamic banking publicationthrough the website of each bank. The method used in this study is an explanatory method.The method used to explain the effect of the variables studies and the relationship between onevariabel with other variables. There are 6 syariah bank used as the samples in this research. Thedata is analyze with linier regresion analysis where previously data tasted by testing classicalassumptiuon including data normality, heteroscedasticity, multicollinearity and autocorrelation.During the observation period, the study shows that data is normally distributed. The result ofthe research indicate that the variables of market concentration is positive but has not significanteffect on ROA. Variable asset growth is positive and has significant effect on ROA.